Protective effect of physical activity on dissatisfaction with body image in children - A cross-sectional study - Marisa J M Monteiro Gaspar (2011)
Objective: To evaluate, in pre-adolescents and adolescents, the frequency of body image dissatisfaction and distortion and to assess the association between these factors and physical activity and body mass index (BMI). Design: Cross-sectional study. Methods: 234 children (10-17 years) from a Porto high school were evaluated. Dissatisfaction with body image (FID) was assessed by Collins' child figure drawings for pre-adolescents and adolescents. FID was calculated as the discrepancy between the "ideal figure" and the "perceived figure". Body image distortion (BID) was calculated as the discrepancy between the "perceived figure" and the "real figure". The Baecke questionnaire was applied to determine the habitual physical activity index (HPAI) of each participant. Results: Girls were more dissatisfied than boys with their body image (68.1% vs 52.9%). A high proportion of students of both genders and age groups revealed BID (71.8%) with 51.3% underestimating their body image and 20.5% overestimating it. A negative association was found between the FID and BID (girls: r = -.259, p = .006: boys: r = -.414, p < .001). High levels of physical activity were associated with a protective effect on FID, OR = 0.38, 95% CI [0.16, 0.87] for 3rd vs 1st quartile of HPAI: OR = 0.29, 95% CI [0.12, 0.86], for 4th vs 1st quartile of HPAI, both adjusted for BMI and gender, but HPAI was not associated with BID. Conclusion: FID and BID are highly frequent and inversely associated. BID increases directly with BMI percentiles in both genders while physical activity has a protective effect on dissatisfaction of body image.